A discrete element/shell finite element coupling for simulating impacts on reinforced concrete structures - Rousseau, Jessica; Marin, Philippe; Daudeville, Laurent; Potapov, Sergueï (European Journal of Computational Mechanics, 2010)
The efficiency of the discrete element method for studying the fracture of heterogeneous media has been demonstrated, but it is limited by the size of the computational model. A coupling between the discrete element and the finite element methods is proposed to handle the simulation of impacts on large structures. The structure is split into two subdomains in each of which the method is adapted to the behaviour of the structure under impact. The DEM takes naturally into account the discontinuities and is used to model the media in the impact zone. The remaining structure is modelled by the FEM. We propose an extension of the coupling procedure to connect the Discrete Element model to shell-type Finite Elements. The efficiency of the coupling method is tested and validated.